The Holocaust and Polish-Jewish Relations in Sociological Studies - Melchior, Małgorzata (Zagłada Żydów. Studia i Materiały, 2008)
The past can be described in different ways by historians and sociologists. They differ in their attitudes toward sources for their studies, and in terms of research sensitivity, which directs their analyses towards given aspects of the past. This text focuses on selected sociological studies of the Holocaust and issues of Polish–Jewish relations (before and during World War II as well as during the immediate postwar years). First I shall refer to sociological works using the historical prospective in their description of Polish–Jewish relations and/or the Holocaust, and, second, to studies (both historical and sociological) which employ categories of sociological analysis in their description. By referring to Nechama Tec's works, I shall present the methodological problems of sociological studies.